Interoperable CNC Machine via Function Block and STEP-NC Data Model for Milling Operation - Minhat, Mohamad (Trans Tech Publications, 2012)
The Function Block Development Kit (FBDK) platform proposed for STEP-NC controller architecture . It can be used to create an open CNC architecture on ISO 14649 and Function Block (IEC 61499). This offers interoperability, portability, and adaptability. The proposed framework consists of three main modules: (1) STEP-NC Interface, (2) Simulator, and (3) Communication. The system will be implemented in CNC controller on actual milling machine. It will simplify the design of CNC machine controller with the architecture layers responsible for data processing, data storage, execution and feedback. This paper also discusses towards the requirements for global interoperable manufacturing for real-life machining system with the architecture layers responsible for data storage, data processing, and execution.